Effective of an Intervention Program on Nurses Practices Concerning Infection Control Measures in Pediatric Surgical Wards - Ali Neamah Mousa, Afifa Radha Aziz, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Infection control has become a major concern in the health-care system, and health-care personnel, especially nurses, are particularly vulnerable to infection. The goal of this study is to see how effective an intervention program is in changing nurses' practices in pediatric surgery wards when it comes to infection management. Methods: This study used a quasi-experimental design for the pre- and post-test. The sample consisted of 40 persons. The intervention group included twenty nurses from the primary pediatric teaching hospital, while the control group included twenty nurses from the pediatric care teaching hospital. The questionnaire's dependability was proven through empirical study, and it was then submitted to specialists for validation. The total number of items in the questionnaire was 49. Self-reports were used to collect data, which was then evaluated using descriptive and inferential statistical data analysis. Results: According to the findings, 70% of nurses had insufficient practices before implementing the intervention program, while 60% of nurses had adequate practices after implementing the program. In the pre-test period of assessment, there is no statistically significant difference between the intervention and control groups (p>0.05). At the post-test measurement period, there is a statistically significant difference between the intervention and control groups (p0.05). Conclusions: In order to improve nurses' infection control practices, an interventional training program is essential. The findings of this study revealed that after receiving training, nurses' infection control practices improved. This study found that the training program is highly successful, and that all nurses should receive infection control training to gain the information and skills necessary to prevent infection in a hospital context. Health-care executives should recognize the importance of establishing rules to improve nurse working conditions and offer the required training to guarantee infection-control strategies are implemented.